Remitan dan Faktor Penentunya Studi Kasus: Migran Risen Kelurahan Jimbaran Kecamatan Kuta Selatan - Octania, Kadek Yomi; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Remittances is a form of migrant attachment to family and region of origin in order to create a welfare for their family and the advancement of the region of origin. This study aims to determine the effect of migrant’s income, the number of household members which is borne in the area of origin, and consumption expenditure of migrant  to remittances.The study was conducted in Jimbaran village with the sampling method is sampling incidental techniques. The total sample of this study is 98 respondents and using path analysis techniques. The result of the analysis showed that migrant’s income, number of household members which is borne in the area of origin, and consumption expenditure of migrant significantly influence on the remittances simultaneously and partially. Migrant’s income significantly influence on  the  consumption expenditure of migrant amounted to 0,859 (P 1 ). The direct effect of migrant’s income,number of household members which is borne in the area of origin, and consumption expenditure of migrant respectively amounted to 0,883 (P 2 ), 0,361 (P 3 ), and -0,728 (P 4 ). The indirect effect of migrant’s income to remittances by the migrant’s consumption expenditure amounted to -0,625 so that the total effect is 0,258.
Keywords: Mobility, Remittances, Income, Consumption, and The Number of Household Members